DISSEMINATED HISTOPLASMOSIS WITH BILATERAL ADRENAL INFILTRATION AND PRIMARY ADRENAL INSUFFICIENCY - Nordin, Hidayatil Alimi Bin Keya; Abdullah, Noor Rafhati Adyani (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Histoplasmosis is a fungal disease caused by Histoplasma capsulatum and characterized by two forms: pulmonary and disseminated histoplasmosis. In the latter form, adrenal infiltration is a common feature, resulting in detection of bilateral adrenal masses radiologically. Bilateral extensive destruction of the adrenal glands results in primary adrenal insufficiency (PAI), which occurs in 5–71% of adrenal histoplasmosis. We present a case of PAI with adrenal histoplasmosis. CASE A 71-year-old male, with underlying diabetes, hypertension, and pulmonary tuberculosis, presented with bloody diarrhea and thrombocytopenia. Multiple ulcers were observed over the dorsal surface of the tongue. The histopathological examination (HPE) of the tongue was consistent with histoplasmosis. Colonoscopy examination was unremarkable. The patient was referred to an infectious disease team and was prescribed a course of itraconazole for six weeks. A year later, he had recurrent bloody diarrhea, and repeated colonoscopy revealed inflamed rectal mucosa. Histopathological examination revealed chronic proctitis with noncaseating granulomas that were consistent with fungal infection. Intravenous amphotericin B was administered, followed by oral isavuconazole and itraconazole. Computed tomography (CT) scan demonstrated enlarged bilateral adrenal glands with the right side measuring 4.9 x 2.6 x 6.8 cm, and the medial limb of the left adrenal gland measuring 4.3 x 2.5 cm. The lateral limb of the left adrenal gland was 3.6 x 2.1 cm. Ten weeks after antifungal therapy was started, CT scan revealed a smaller left adrenal lesion, but the right adrenal lesion remains unchanged. Short synacthen test showed PAI with peak cortisol 246 nmol/L, ACTH 20.3 pmol/L (1.6-13.9). He is awaiting adrenal biopsy pending urinary metanephrines. Glucocorticoid replacement was initiated. Antifungal therapy would be continued for no less than one year. CONCLUSION Adrenal histoplasmosis is common and histopathological analysis is crucial in managing such cases. It is important to be vigilant about infections like histoplasmosis as a potential cause of PAI. Delay in treatment could result in life-threatening consequences.